The Contract Of Mudharabah (Qiradh) And Musyarakah (Syirkah) In Fiqh Muamalah - Khailila Salsabila; Nurhidayati Maharani; Muhammad Nur Iqbal (Jurnal Multidisiplin Sahombu, 2025)
Contract Mudharabah and Musyarakah is form Work The same business between two parties or more , with runway strong law​ from the Qur'an and Hadith. Research This use approach normative with focus on study Islamic law related contract Mudharabah and Musyarakah . Research data obtained through method studies library research , which involves search primary and secondary sources in the form of literature jurisprudence muamalat , fatwa of the National Sharia Council (DSN), Tafsir of Sheikh Abdul Halim Hasan, as well as document related implementation contract in institution Islamic finance . Analysis done in a way descriptive qualitative For understand runway law , implementation , and settlement dispute in second contract said . The agreement Musyarakah involving two parties or more For Work The same in a business with distribution profit based on agreement . While that , Mudharabah involving capital owners ( shahibul mal ) and managers ( mudharib ) who share profit in accordance agreed portion . Implementation​ contracts This Lots applied in product sharia financing , such as savings , deposits , up to working capital financing . Completion dispute in second contract the done through peace or court in accordance principle Islamic law . This article to study runway laws , conditions , and implementation contract Mudharabah and Musyarakah , including settlement dispute related .